The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/en14020294
|View full text |Cite
|
Sign up to set email alerts
|

Internal Wind Turbine Blade Inspections Using UAVs: Analysis and Design Issues

Andrius Kulsinskas,
Petar Durdevic,
Daniel Ortiz-Arroyo

Abstract: Interior and exterior wind turbine blade inspections are necessary to extend the lifetime of wind turbine generators. The use of unmanned vehicles is an alternative to exterior wind turbine blade inspections performed by technicians that require the use of cranes and ropes. Interior wind turbine blade inspections are even more challenging due to the confined spaces, lack of illumination, and the presence of potentially harmful internal structural components. Additionally, the cost of manned interior wind turbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 76 publications
(120 reference statements)
0
12
0
Order By: Relevance
“…In the last few decades, the use of wind turbines has increased significantly. For example, in the U.S. alone, the share of wind turbines was 10% in 2020, and is estimated to grow close to 20% by 2030 [72]. Despite the inherent benefits of using wind turbines, maintenance is still a challenging topic.…”
Section: Inspection Of Wind Turbinesmentioning
confidence: 99%
See 4 more Smart Citations
“…In the last few decades, the use of wind turbines has increased significantly. For example, in the U.S. alone, the share of wind turbines was 10% in 2020, and is estimated to grow close to 20% by 2030 [72]. Despite the inherent benefits of using wind turbines, maintenance is still a challenging topic.…”
Section: Inspection Of Wind Turbinesmentioning
confidence: 99%
“…Therefore, the blades are at great risk of failure [74]. Furthermore, wind turbine's components can contain manufacturing defects as well as damages during operation by lightning strikes, collision with birds and insects, corrosion, and the accumulation of dirt or ice [72]. Surveys conducted on 700 on-shore wind turbines located in Sweden in 1997-2005 have demonstrated that 13.4% of the failures are related to the rotor blades [74].…”
Section: Inspection Of Wind Turbinesmentioning
confidence: 99%
See 3 more Smart Citations